2019
DOI: 10.1016/j.stemcr.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GATA2 Enhances Development and Maintenance of Human Embryonic Stem Cell-Derived Hematopoietic Stem Cell-like Progenitors

Abstract: Summary GATA2 is essential for the endothelial-to-hematopoietic transition (EHT) and generation of hematopoietic stem cells (HSCs). It is poorly understood how GATA2 controls the development of human pluripotent stem cell (hPSC)-derived HS-like cells. Here, using human embryonic stem cells (hESCs) in which GATA2 overexpression was induced by doxycycline (Dox), we elucidated the dual functions of GATA2 in definitive hematopoiesis before and after the emergence of CD34 + CD45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…Cells have even been generated through processes that recapitulate in vitro the EHT that takes place in the AGM as a way to ensure acquisition of stemness to produce pluripotent HSCs with the capacity to colonize hematopoietic sites. However, these cells still lack a robust capacity to engraft in a host (Wang et al, 2005;Lengerke et al, 2009;Doulatov et al, 2013;Riddell et al, 2014;Ruiz et al, 2019;Zhou et al, 2019). The first experiment that succeeds to produce engraftable HSCs from iPS cells achieved this by driving differentiation in vivo through teratoma formation, but even in this case, the efficiency was very low with less than 1-2% of engraftment and relied on complex procedures and cocktails of cytokines to achieve this (Amabile et al, 2013;Suzuki et al, 2013;Philipp et al, 2018).…”
Section: In Vitro Hematopoietic Transdifferentiation From Ips/es Cellmentioning
confidence: 99%
“…Cells have even been generated through processes that recapitulate in vitro the EHT that takes place in the AGM as a way to ensure acquisition of stemness to produce pluripotent HSCs with the capacity to colonize hematopoietic sites. However, these cells still lack a robust capacity to engraft in a host (Wang et al, 2005;Lengerke et al, 2009;Doulatov et al, 2013;Riddell et al, 2014;Ruiz et al, 2019;Zhou et al, 2019). The first experiment that succeeds to produce engraftable HSCs from iPS cells achieved this by driving differentiation in vivo through teratoma formation, but even in this case, the efficiency was very low with less than 1-2% of engraftment and relied on complex procedures and cocktails of cytokines to achieve this (Amabile et al, 2013;Suzuki et al, 2013;Philipp et al, 2018).…”
Section: In Vitro Hematopoietic Transdifferentiation From Ips/es Cellmentioning
confidence: 99%
“…N = 3 replicates; * P < 0.05, ** P < 0.01, *** P < 0.001, **** P < 0.0001; ns, not significant cytometry. The results showed that ALA-treated cocultures had more CD38 − CD90 + HSC phenotype-like cells 22 within the CD34 + CD43 + CD45 + populations ( Fig were counted. One thousand CD34 + CD43 + hematopoietic stem/progenitor cells on Day 14 were sorted into each replicate.…”
Section: Ala Promotes Production Of Hemogenic Endothelium Cells and Hmentioning
confidence: 99%
“…We have used cocultures of hPSCs with AGM-S3 stroma cells to explore the hematopoiesis of hPSCs. 17,21,22 Previous reports show that ALA affects intracellular ROS levels and apoptosis. 23,24 Upon irradiation, ALA protects HSCs in bone marrow and improves survival of animals 25 ; in addition, it can partially rescue the loss of HSCs caused by high ROS levels in GRK6 − /− mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is an important member of the CKI family (24), the function of p21 in hematopoiesis has not yet been explored in an hESC-based in vitro system for hematopoiesis. We used the PB-Tet-on-OE vector system to establish an inducible p21/hESC line to characterize the roles of p21 (CDKN1A) in the AGM-S3 co-culture system using similar methods to those reported previously (10,18,25). This approach should confer much higher accuracy than a conventional expression system to test the effects of p21 on multiple stages, especially to uncover its roles in blockage effects of RUNX1b on hematopoiesis (10).…”
Section: Discussionmentioning
confidence: 99%